ANGIOGRAPHIC FINDINGS OF HEPATOCELLULAR CARCINOMA IN SIRIRAJ HOSPITAL - Chutakiat, KRUATRACHUE; Krisdee, PRABHASAVAT; Kriengkrai, IEMSAWATDIKUL; Saroj, VANAPRUNKS; Walailak, CHAIYASOOT; Kanjana, DANPUKDEE (The ASEAN Journal of Radiology, 2023)
Five years collection of 126 cases of celiac and hepatic angiography of hepatocellular carcinoma were done and analysed in the aspects of sex, age and angiographic findings, such as, neovascularity, vascular distortion, etc. The most common finding was neovascularity(88%), the least findings were avascularity(5%), and normal angiographic finding(5%). Comparison between eighteen cases of pathological diagnosis with the other study was also performed.